1989/1991: a wave of partially victorious democratic revolutions, which did not prevent defeat in the face of economic-social counter-revolution - Arcary, Valério (2009)
Fortunately, there are discussions that are resolved by history. There no longer seems to be any point in debating whether or not there was a capitalist restoration after the fall of the Berlin Wall. At least with regard to the USSR and Eastern Europe, since in relation to China and Cuba there are not a few those on the left and inspired by Marxism who are still convinced that they would be States engaged in some type of transition, even if it is in the very long duration, to socialism.